Microplastic and tar pollution on three Canary Islands beaches: An annual study. Issue 2 (April 2018) - Herrera, A.; Asensio, M.; Martínez, I.; Santana, A.; Packard, T.; Gómez, M.
Abstract: Marine debris accumulation was analyzed from three exposed beaches of the Canary Islands (Lambra, Famara and Las Canteras). Large microplastics (1–5 mm), mesoplastics (5–25 mm) and tar pollution were assessed twice a month for a year. There was great spatial and temporal variability in the Canary Island coastal pollution. Seasonal patterns differed at each location, marine debris concentration depended mainly of local-scale wind and wave conditions. The most polluted beach was Lambra, a remote beach infrequently visited. The types of debris found were mainly preproduction resin pellets, plastic fragments and tar, evidencing that pollution was not of local origin, but it cames from the open sea. The levels of pollution were similar to those of highly industrialized and contaminated regions. This study corroborates that the Canary Islands are an area of accumulation of microplastics and tar rafted from the North Atlantic Ocean by the southward flowing Canary Current. Highlights: Marine debris in the Canary Islands was documented over an annual cycle. High seasonal variability above an order of magnitude was found. Coastal orientation, local wind and waves determined debris concentration. Tar and resin-pellet pollution was high in two beaches. The type of debris found indicated an open-sea source.